Industrialised building system versus conventional system in waste production toward sustainability in construction - Noor Asyiq, Mohd Johari (2012)
Industrialized Building System (IBS) is a system where buildings are reduced to a number of common parts, where most of it can be prefabricated in long term production runs, frequently away from the construction site. Lately, Malaysia government strongly support the usage of IBS in construction industry due to its quality assurance, shorter construction period, cleaner site condition, safer working environment and reduction in labor dependency. In this study, the advantage of IBS is focused on the reduction and management control of wastes, or basically minimizing wastes at the construction site which lead to sustainability in construction. Efforts to make IBS a success are not sufficient without the participation and support from the private sector. Questionnaire surveys were undertaken throughout the industry role players such as developer, consultant, contractor and government bodies. The analysis result showed that the involvement of the respondents in IBS was high and the awareness level was also considerably high. The use of steel in the conventional construction create the most waste and by using IBS the saving in material amount to approximately 54.83%. On the other hand, the set of timber does not show any significant material savings in either the conventional or IBS construction.